2014
DOI: 10.1155/2014/786947
|View full text |Cite
|
Sign up to set email alerts
|

The Role of IL-17 Promotes Spinal Cord Neuroinflammation via Activation of the Transcription Factor STAT3 after Spinal Cord Injury in the Rat

Abstract: Study Design. In this study, we investigated the role of IL-17 via activation of STAT3 in the pathophysiology of SCI. Objective. The purpose of the experiments is to study the expression of IL-17 and related cytokines via STAT3 signaling pathways, which is caused by the acute inflammatory response following SCI in different periods via establishing an acute SCI model in rat. Methods. Basso, Beattie, and Bresnahan hind limb locomotor rating scale was used to assess the rat hind limb motor function. Immunohistoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…Bladder compression urination was recorded twice daily. The BBB (Basso, Beattie, and Bresnahan) scoring method [12] (21 levels) was used as a functional assessment to evaluate behavior and hindlimb motor function in the rats before and after SCI. The evaluations were performed before injury and on postoperative days 1, 3, and 7, and each index was measured three times.…”
Section: Construction and Clinical Evaluation Of A Rat Sci Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Bladder compression urination was recorded twice daily. The BBB (Basso, Beattie, and Bresnahan) scoring method [12] (21 levels) was used as a functional assessment to evaluate behavior and hindlimb motor function in the rats before and after SCI. The evaluations were performed before injury and on postoperative days 1, 3, and 7, and each index was measured three times.…”
Section: Construction and Clinical Evaluation Of A Rat Sci Modelmentioning
confidence: 99%
“…In the resting state, NF-κB binds to its inhibitory monomer (IκB) [9]. The protein remains in the cytoplasm at rest but is activated by SCI in nerve cells, glial cells, and vascular endothelial cells [10][11][12]. Activated NF-κB enters the nucleus and binds to the κB sequence in the promoter or enhancer of the target gene to promote the expression of a large number of inflammatory cytokines, inflammatory chemokines, and adhesion molecules that target gene release, such as IL-1, TNF-α, IL-6, IL-8, and ICAM-1.…”
Section: Introductionmentioning
confidence: 99%
“…SCI is severe traumatic injury to the spinal cord (SC) that usually results in sensation disability and paralysis [87,93]. There is currently no effective therapy [87].…”
Section: Scimentioning
confidence: 99%
“…Given that the primary injury is always unexpected, the SC can be protected or rescued only during the secondary injury phase [95]. However, the mechanisms underlying secondary injury are not fully defined [93][94][95][96]. Recovery following SCI is impaired in IFN-gR À/À mice, and this impairment is linked to reduced expression of the trafficking molecule ICAM-1 and the chemokines CXCL9 and -10 by the CP, which results in reduced T cell and monocyte entry into the CSF [46].…”
Section: Scimentioning
confidence: 99%
“…During acute phase, SC expresses high amounts of Th1 phenotype which is mainly regulated by IL-2, IL-12 and IFNy. Moreover, in subacute phases IL-4, IL-13, IL-10, IL-17 and IL-23 cytokines are found in plasma and spleen, indicating the presence of Th2, Treg and Th17 profiles as an inefficient compensatory mechanism [93,94]. Accordingly to this, for the last 10 years experimental findings have shown that T lymphocytes are not just pathogenic but beneficial.…”
Section: Lymphocytes As Double-edged Sword In Spinal Cord Injurymentioning
confidence: 90%